JERD GURB: DEVELOPMENT OF ISAN THAI FOLK GAMES TRANSFORMED TO YOUTH LEISURE SPORTS - Tongterm, Tachapon; Phongthanu, Metawut; Kaewma, Jeeranan (Journal of Faculty of Physical Education, 2024)
The purposes of this research were as follows. 1) To design and develop leisure sports for youths between the ages of 18-24 years: At this stage, an action research design was employed through the 3 rounds of experimentation and development process. The samples consisted of 70 healthy youth volunteers aged between 18-24 years. 2) To assess the quality of Jerd Gurb, leisure sports for youths developed by the research team: The samples used in the quality assessment of Jerd Gurb were as follows: 2.1) 9 experts in sports science and physical education using the index of item-objective congruence (IOC) and 2.2) 40 athletes and spectators participating in Jerd Gurb (35 athletes and 5 spectators) using the satisfaction assessment to assess the samples’ satisfaction after participating in the 10th edition of Sports Science Network Sports Expo, Rajabhat University of Thailand Group, 2023. The research findings were as follows. 1) Jerd Gurb, leisure sports for youths between the ages of 18-24 years with a field size, equipment, methods of playing, rules and regulations for playing, number of players, scoring criteria, fouls, and clear methods for deciding the winner and the loser was obtained. 2) The quality of Jerd Gurb, leisure sports developed by the research team, assessed by 9 experts in sports science and physical education showed that the IOC was was 0.89, which was acceptable. 3) The quality of Jerd Gurb assessed by 40 athletes and spectators revealed that the satisfaction mean score was 4.47, which was at a high level.